Benefits and Value of Big Trees in Urban Area: A Study in Bang Kachao Green Space, Thailand - Yotapakdee, Teeka; Asanok, Lamthai; Kamyo, Torlarp; Norsangsri, Monton; Karnasuta, Napak; Navakam, Suwit; Kaewborisut, Chidchai (Environment and Natural Resources Journal, 2018)
Green Space is very important for the conservation of biodiversity in the urban areas of Thailand. In the case of Bang Kachao, Green Space has been improved by the development of gardens in the city. The objective of this study focused on an evaluation of the benefits of big trees in the urban area at Bang Kachao Green Space, Samutprakan province. Data was collected from six types of tree habitat classified as road side, abandoned area, public area, private area, temple area, and park located across six sub districts of Bang Kachao. Data were analyzed to evaluate the monetary value of big trees from direct and indirect benefits in three parts consisting of timber value, carbon credits value, and spiritual value. The results reveal that the most valuable big trees are in the parks, followed by temple area, road side, private area, abandoned area, and public area respectively. The total monetary value of big trees was 23,447 USD of which timber value was 13,844 USD, carbon credits value was 7,309 USD, and spiritual value was 2,294 USD. The evaluation suggests that management of high value big trees in park, temple, and road side areas is important from a stakeholder perspective. The recommendations based on this study will help develop appropriate policies for sustaining ecosystem services and contributions to human wellbeing.